DRUG-CARRIER PROPERTY OF ALBUMIN MICROSPHERES IN CHEMOTHERAPY. III. EFFECT OF MICROSPHERE-ENTRAPPED 5-FLUOROURACIL ON EHRLICH ASCITES CARCINOMA IN MICE - SUGIBAYASHI, KENJI; KATO, YOSHIO; MORIMOTO, YASUNORI; NADAI, TANEKAZU; AKIMOTO, MASAYUKI (Journal of Pharmacobio-Dynamics, 1979)
To examine the possibility of utilizing albumin microspheres as drug-carriers, an in vitro release of 5-fluorouracil (5-FU) from albumin microspheres was examined and the effect of intraperitoneally injected drug-carrying microspheres on Ehrlich ascites carcinoma in mice was studied. In vitro release characteristics determined by dialysis experiments showed that 5-FU release continued over one week. We also noted that drug release in the peritoneum of ascites-bearing mice continued over one week and that their life-span increased. Furthermore, the microspheres were phagocytized in vivo by the ascites cells. Our results suggest that albumin microspheres containing 5-FU may represent an effective system of drug delivery with prolonged action.